Vocation Science Axiologi in Kiai Sholeh Darat’s Perspective - Ahmad Umam Aufi; Sri Tutie Rahayu; Ali Imron (Kutubkhanah, 2026)
The focus of Presidential Regulation (Perpres) No. 68 of 2022 on revitalizing vocational education seems to prioritize economic goals over the important spiritual aspects of vocational science. This study offers the views of Kiai Sholeh Darat, a great teacher of Ulama in the archipelago on vocational science axiology as an alternative to revitalizing the spiritual aspects of vocational education. This study also aims to photograph the position of vocational science axiological and reconstruct the spiritual aspects of vocational science to revitalize vocational education. The research method used is a method of studying the thoughts of figures with a philosophical and historical approach. Fazlur Rahman's double movement theory is used as an analytical knife in presenting data. The results of this study show that vocational science is axiologically oriented towards the sustainability of a country and the benefit of world life as a charity field for the afterlife. Both can be reconstructed as monotheistic values and worldly benefit orientations. The value of monotheism is the foundation and main goal in the revitalization of vocational education. World benefit orientation is only a means in the spiritual process of worship drawing closer to God. Kiai Sholeh Darat's view on the vocational science axiology as a process of revitalizing spiritual aspects in the implementation of vocational education can be used as an alternative in encouraging the realization of Presidential Regulation No. 68 of 2022 concerning on the revitalization of vocational education